TRIM28 regulates RNA polymerase II promoter proximal pausing and pause release - Bunch, Heeyoun (2014)
Promoter proximal pausing of RNA polymerase II (Pol II) is a major checkpoint in transcription. An unbiased search for novel human proteins that could regulate paused Pol II at the HSPA1B gene identified TRIM28. In vitro analyses indicated HSF1-dependent attenuation of Pol II pausing upon TRIM28 depletion, whereas in vivo data revealed de novo expression of HSPA1B and other known genes regulated by paused Pol II upon TRIM28 knockdown. These results were supported by genome-wide ChIP-sequencing analyses of Pol II occupancy that revealed a global role for TRIM28 in regulating Pol II pausing and pause release. Furthermore, in vivo and in vitro mechanistic studies suggest that transcription-coupled phosphorylation regulates Pol II pause release by TRIM28. Collectively, our findings identify TRIM28 as a novel factor that modulates Pol II pausing and transcriptional elongation at a large number of mammalian genes.